Microsoft Windows Vista administration - Velte, Anthony T.; Glendenning, Dennis R. (Dennis Robert); Velte, Toby J. (New York ; London : McGraw-Hill, 2007)
A guide to Windows Vista administration describes how to design and implement installation and migration plans, create network connections, set up Internet services, use remote access features, and secure PCs and networks.
Behavior 456 -- Windows Mobility Center 457 -- Using the Windows Mobility Center 458 -- Tablet PCs 458 -- The Pen 458 -- Tablet PC Applications 462 -- Sync Center 471 -- Sync Modes 472 -- Synchronization 473 -- Conflicts 474 -- Synching Devices 474 -- Managing Mobile Users 475 -- DHCP 475 -- Alternate Private IP Addresses 477 -- Managing Power Plans with Group Policy 478 -- 14 Supporting Vista 483 -- MMC 3.0 484 -- The MMC Interface 484 -- Adding and Removing Snap-ins 484 -- Setting the Parent Node 485 -- Backing Up and Restoring 486 -- System Restore 487 -- Backup 490 -- Shadow Copies 492 -- Configuration Tools 494 -- Computer Management 494 -- Startup Applications 497 -- Windows PowerShell 499 -- New Command-Line Tools 502 -- Support Tools 503 -- Event Viewer 504 -- Device Manager 518 -- Performance Monitoring 525 -- Performance Information and Tools 525 -- Using Local and Group Policies 532 -- Multiple Local Group Policy Objects 533 -- New Administrative Templates 537 -- 15 Troubleshooting 539 -- Built-in Diagnostics 540 -- Hardware, Performance, and Memory Diagnostics 541 -- Network Diagnostics 542 -- Hardware Problems and Diagnostics 543 -- Event Viewer 543 -- Device Manager 546 -- Memory Diagnostic Tool 546 -- Registry Helpers 546 -- Printing Problems and Diagnostics 549 -- Installation Issues 550 -- Printing Problems 552 -- Performance Problems 553 -- Printer Permissions 5
Includes index.
1 2
Keywords: Microsoft Windows (Computer file); Computer networks -- Management